2016
DOI: 10.5194/cp-12-1389-2016
|View full text |Cite
|
Sign up to set email alerts
|

Extreme storms during the last 6500 years from lagoonal sedimentary archives in the Mar Menor (SE Spain)

Abstract: Abstract. Storms and tsunamis, which may seriously endanger human society, are amongst the most devastating marine catastrophes that can occur in coastal areas. Many such events are known and have been reported for the Mediterranean, a region where high-frequency occurrences of these extreme events coincides with some of the most densely populated coastal areas in the world. In a sediment core from the Mar Menor (SE Spain), we discovered eight coarse-grained layers which document marine incursions during perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…BP. The latter two periods of enhanced Mediterranean sourced precipitation correspond well with times of dominant positive modes of the North Atlantic Oscillation (NAO + ) [ 87 ] and reduced Western Mediterranean storminess [ 88 , 89 ] ( Fig 4 ). The Western Mediterranean storminess record, however, shows higher variability, which might be related to its distant location in the Gulf of Lions.…”
Section: Discussionmentioning
confidence: 72%
“…BP. The latter two periods of enhanced Mediterranean sourced precipitation correspond well with times of dominant positive modes of the North Atlantic Oscillation (NAO + ) [ 87 ] and reduced Western Mediterranean storminess [ 88 , 89 ] ( Fig 4 ). The Western Mediterranean storminess record, however, shows higher variability, which might be related to its distant location in the Gulf of Lions.…”
Section: Discussionmentioning
confidence: 72%
“…These results corroborate the marine origin of these sediments as revealed by the binocular microscope observations mainly due to the existence of shell debris and confirmed by the grain-size distributions. Therefore, we suggested that the first component agreed with the fine fraction of the sediment, which is mainly composed of various types of clay minerals, usually abundant in surface sediments (De Lazzari et al, 2004). On the other hand, factor 2 ( Fig.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 87%
“…This contribution can reach 1863 t yr −1 [95]. Contributions from the Mediterranean or exchanges through the inlets have not been studied in depth, but there is evidence that they can be significant throughout the recent history of the Mar Menor lagoon, especially during extreme storm events [96]. Sedimentation rates have changed during the evolution of the Mar Menor lagoon linked to human uses in the drainage basin, and have increased with time, from 30 mm/century before the Middle Age to more than 30 cm/century in the 20th century, particularly due to deforestation and agricultural practices [97].…”
Section: Discussionmentioning
confidence: 99%